Classification of Meandering Rivers: Interpreting the Morphological River by Using the Planimetric Characteristics - Sukamto, Yuri; Tallar, Robby Yussac; Trisina, William (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2015)
It must be recognized that rivers differ among themselves, and through time,one river can vary significantly in itsdownstream direction. Most of the riversclassification was published by US or European researchers. In fact, these classifications of the river cannot be applied thoroughly to other regions such Asian Countries due to its differentcharacteristics and situations. Therefore, the general purpose of thisresearch is to establish a simple and easy-touse practice in interpreting the morphological aspect of river by using planimetric characteristics. We selected four major rivers to develop the conceptual model for classification of meandering rivers in Borneo (Kalimantan) Island. Further, we divided themeandering rivers in Borneo Island by three zones to get the informed data in detail. Based on the results, the variability variesin all planimetric characteristics except the slope, which is considered as conformity.